2022
DOI: 10.3390/vaccines10081311
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinations Status against Vaccine-Preventable Diseases and Willingness to Be Vaccinated in an Italian Sample of Frail Subjects

Abstract: Background: Study aim was to investigate the vaccination status against vaccine-preventable diseases (VPD) of frail adults during the SARS-CoV-2 pandemic and, for those subjects eligible for at least one vaccine, with respect to the recommended vaccination in line with the Italian National Vaccination Prevention Plane (NPVP), to explore the willingness to be vaccinated. Methods: A cross-sectional study was carried out among adults aged ≥ 60, immunocompromised or subjects affected by chronic conditions. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
(45 reference statements)
1
3
0
Order By: Relevance
“…Surprisingly, in our study, age, chronic diseases, and BMI were not associated with the development of side effects. In fact, elderly individuals and those with chronic diseases and high BMI are known to be characterized by weak immune-system reactions, confirming previous results of multiple studies that reported that people in these categories developed adverse effects less frequently than those in other age groups [45][46][47][48].…”
Section: Discussionsupporting
confidence: 87%
“…Surprisingly, in our study, age, chronic diseases, and BMI were not associated with the development of side effects. In fact, elderly individuals and those with chronic diseases and high BMI are known to be characterized by weak immune-system reactions, confirming previous results of multiple studies that reported that people in these categories developed adverse effects less frequently than those in other age groups [45][46][47][48].…”
Section: Discussionsupporting
confidence: 87%
“…Difficulties in access to care for chronic diseases during the COVID-19 pandemic have been pointed out as “the other side of the coin” of this global problem, generating an additional burden on the health systems [1] , [2] . Other authors have reported changed in influenza and pneumococcal vaccination during COVID-19 pandemic [12] , [13] , [14] , which had been due to multiple causes. Interestingly, in two of these studies [13] , [14] an increase in the attempt to uptake a pneumococcal vaccine has been observed.…”
Section: Discussionmentioning
confidence: 98%
“…Given the fact that there were no problems with vaccine supplies during the period analyzed, other factors are needed to explain the lack of adherence to these important prevention strategies. Accordingly, a recent systematic review analyzed the barriers to vaccine access in Latin America [12] . The authors found that many factors influence this issue, including economic, financial, educational and cultural barriers, and low confidence in the efficacy and safety of vaccines among the main obstacles.…”
Section: Discussionmentioning
confidence: 99%
“…However, a critical aspect is the patients’ adherence; there are several motivations behind the decision making to not get vaccinated, such as safety and efficacy concerns, low perceived risk of illness, lack of knowledge, and lack of information [ 12 , 13 , 14 ]. To the best of our knowledge, the number of studies in the current literature that have been conducted to assess the knowledge, attitudes, and behaviors of the recommended vaccines among individuals with chronic medical conditions in Italy are lacking [ 15 , 16 , 17 ]. Since it is important to fill the gap in the literature and considering that this understanding is crucial to increase vaccine uptake among this population, the objectives of the present cross-sectional survey were to investigate the level of knowledge, the attitudes, and the coverage with respect to recommended vaccines against seasonal influenza, pneumococcal, meningococcal, and HZ among patients with chronic medical conditions in Italy and to determine the influencing factors.…”
Section: Introductionmentioning
confidence: 99%